MENELUSURI JEJAK RELIGIUS PENYAIR BINHAD NURROHMAT: MEMBACA HABITUS, ARENA, DAN MODAL PESANTREN - fatoni, Akhmad (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2019)
This study aims to assess the condition of the social arena poet who became background Binhad Nurrohmat practice. This study uses the paradigm of sociology of literature with a focus on sociological theory Pierrie Bourdieu is arena of cultural production. This research is a qualitative research with the object of research is poet Binhad Nurrohmat. As a field research, this research was conducted in Rejoso, Jombang, as the author's residence. Data collection methods in this study are by: a) in-depth interviews, b) literature, and c) documentation. The results showed that the change in the pattern of a pattern of poetic Binhad Nurrohmat erective contemplative religious background as they have. When used to be students, religious background (pesantren) is not flashy, just implicit in the work and literacy movements (NU Miring and Kuburan Institut). When the religious background Binhad Nurrohmat reached its peak (when it became pesantren Darul Ulum, Peterongan Jombang, Jawa Timur) makes poetic patterns change. Keywords: social production arena, pesantren, erective, contemplative